P083/O23 Novel subclass of non-classical monocytes are critical for inflammation. (March 2019) - Montgomery, AB; Homan, PJ; Winter, D; Perlman, HR
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Monocytes in mice are distinguishable by expression of Ly6c. Ly6c hi (classical) monocytes are associated with pro-inflammatory responses, while Lyc6 lo (non-classical) are involved in patrolling endothelial membranes. We have previously shown that depletion of monocytes prevents serum transfer induced arthritis (STIA) in mice, and that Lyc6 lo monocytes are the critical population. Objectives: We aim to contrast Ly6c lo monocytes from the circulation, lining vessels, and tissue to determine their involvement in inflammation. Methods: Female 8–10 week old NR4A1 -/-, CX3CR1 ERCre.zsGFP, and C57Bl/6 mice were used in all studies. CX3CR1 ERCre.zsGFP were utilized for cell tracking studies and joint shielded bone marrow chimeras via administration of tamoxifen (tam). Intravascular monocytes were identified by I.V. anti-CD45 labeling before perfusion. STIA was induced via I.V. KBxN sera. Cell populations were quantified by flow cytometry and FACS sorted for RNA-seq. Monocytes were identified CD45 + CD11b + Ly6G - TIM4 - CD64 - Ly6c lo and subdivided into intravascular (labeled, CD43 + ), trans-vascular (labeled CD43 - ) and extravascular (no label). Results: NR4A1 -/- mice retain only 5% of circulating Ly6c lo monocytes but all joint Ly6c lo cells. STIA was comparable in NR4A -/- and C57Bl/6 mice suggesting circulating Ly6c lo are redundant. Transcriptional profiling of Ly6c lo cells identified distinct pathways enriched in upregulated genes between Ly6c lo from joint and blood. In the joint we identified three populations of Ly6C lo monocytes: extravascular unlabeled cells, labeled trans-vascular cells, and labeled intravascular cells adherent to endothelium. Mice given tam D8 of gestation had GFP + microglia only, whereas D15 tam induced GFP + synovial macrophages and unlabeled Ly6c lo monocytes. Both labeled Ly6c lo populations were GFP -, indicating unlabeled and unlabeled Ly6c lo arise from different progenitors. This was confirmed by bone marrow chimera studies showing labeled Ly6c lo cells are replenished from blood monocytes. Clodronate loaded liposomes depleted labeled CD43 + cells but did not affect CD43 - cells or unlabeled cells. With with our previous finding that clo-lip prevents STIA, these suggest adherent CD43 + Ly6c lo cells are essential. This is supported by the finding that labeled Ly6c lo monocytes expand rapidly during the first 1 hour of STIA. Adherent CD43 + cells expand especially rapidly, increasing in population size by 30x. Conclusions: We have identified and described two previously uncharacterized populations of Ly6c lo cells in the joint- intra-vascular adherent and trans-vascular which have distinct origins and phenotype from both extravascular and circulating Ly6c lo . The findings presented here strongly suggest adherent Ly6c lo monocytes are a key effector cell in inflammatory arthritis. Disclosure of Interest: None declared.